Comparison of Ascent Hill Climbing Algorithm And Simple Hill Climbing Algorithm Solving The 8-Puzzle Case - Padma Mike Putri M (IJISTECH (International Journal of Information System and Technology), 2022)
Puzzle 8 game is a game that shifts numbers in the form of a box consisting of 9 squares arranged with numbers 1 to 8 based on the order of count and there is an order of 3x3. This form of game is very easy to complete if you follow the rules that have been applied to the algorithm. Comparison of the ascent hill climbing algorithm and the simple hill climbing algorithm. The purpose of this algorithm is to help children who are just learning to arrange a sequence of numbers so that they explore brain power and increase imagination for children. The difference between the ascent hill climbing algorithm and the simple hill climbing algorithm lies in the search movement which does not start from the far left position but the next movement is searched based on the best heuristic value. To obtain the Goal, a systematic process is needed to make it easy and fast in finding solutions so as to save time in finding the final goal.